Negotiating crisis in the Social Media environment: Evolution of crises online, gaining credibility offline - PANG, A. (Institutional Knowledge at Singapore Management University, 2014)
Purpose– The aim of this paper is to examine how crises can be triggered online, how different social media tools escalate crises, and how issues gain credibility when they transit to mainstream media.Design/methodology/approach– This exploratory study uses the multiple case study method to analyze five crises, generated online, throughout their life-cycles, in order to build analytic generalizations (Yin).Findings– Crises are often triggered online when stakeholders are empowered by social media platforms to air their grievances. YouTube and Twitter have been used to raise issues through its large user base and the lack of gatekeeping. Facebook and blogs escalate crises beyond the immediate stakeholder groups. These crises are covered by mainstream media because of their newsworthiness. As a result, the crises gain credibility offline. Mainstream media coverage ceases when traditional news elements are no longer present.Research limitations/implications– If crises are increasingly generated online, this study aims to apply a framework to manage the impact on organizations.Practical implications– How practitioners can use different new media tools to counter crises online and manage the transition of crises to mainstream media.Originality/value– This is one of the first few studies that analyses how organizational crises originate online, gain traction and get escalated onto mainstream media. Understanding what causes crises to trigger online and gain legitimacy offline will enable practitioners to engage in effective crisis management strategies.